The Effect of External Debt in the Economic Growth of Pakistan - Asghar, Muhammad Saad (ABC Journal of Advanced Research, 2016)
In this study we examine the effect of external debt with the economic growth of Pakistan. External debt is a debt which is held by the creditors of foreign countries in the world. Time series data is collected from the World Bank site for the last thirty years ranges from 1986-2015. Statistics analysis and ordinary least square regression is performed through a descriptive statistical table. To check the relationship between economic growth and external debt OLS model is used. GDP is our dependent variable. Gross domestic saving, gross capital formation and external Debt stock is our independent variable. The results show that the huge amount of number of GDP of country is backed by external debt.